THE IMPACT OF GENERATIONAL CHARACTERISTIC, WORKLOAD WORK CONFLICT, LEADERSHIP ON JOB STRESS - SALAMAH, FITRIANI (INDONESIAN RESEARCH SOCIETY, 2018)
The purpose of this study is to determine the effects of generational characteristic, workload,work conflict, leadership, and work culture on work stress. Respondents in this study areSETDA employees including two criteria. First, those born in 1965-1979 and 1980-1994.Secondly, those who work in the SETDA office. Based on the results of research and dataanalysis using multiple regression with dummy variables, the results of this study shows thatgenerational characteristic, leadership and work culture have no effect on work stress.Thus, workload and work conflict has a positive effect on work stress. The implication of theresults of this study, that SETDA needs to strengthen the work culture and maintain goodvalues such as giving support from fellow employees and leaders. Because with strongculture can to reduce work stress among employees. In addition, SETDA needs to improvethe work system like felt by some employees there